Senegalia propinqua (Leguminosae: Mimosoideae), a new species from the Yuanjiang dry-hot valley in south-central Yunnan Province, China - Bai, Lin; Maslin, Bruce; Xia, Nianhe (Phytotaxa, 2021)
Senegalia propinqua (Leguminosae: Mimosoideae), a new species from the Yuanjiang dry-hot valley in south-central Yunnan Province, China is described and illustrated. It is compared with S. kunmingensis, S. macrocephala and S. teniana. A distribution map of the four species is provided.